PERAN GURU PAI DALAM MENINGKATKAN PRESTASI BELAJAR SISWA MASA PANDEMI COVID-19 DI SMAN 5 KOTA BOGOR (KELAS X/SEPULUH) - Lu'lu Ul Mufidah (Universitas Pahlawan Tuanku Tambusai, 2022)
Coronaviruses are a group of viruses that can cause disease in animals or humans. A new type of coronavirus that was discovered to cause the disease Covid-19. Covid-19 is an infectious disease caused by a newly discovered type of coronavirus. the covid-19 virus was first discovered in Wuhan, China in December 2019 and is now a pandemic that is happening in many countries around the world. Which resulted in all activities being hampered especially in the world of education. Impact on education the government has temporarily closed all educational installations, across the country to limit the spread of the coronavirus and as of March 14, 2020, around 420 million children were out of school. More than 13 countries have temporarily closed all their schools. Likewise in Indonesia, in responding to the Covid-19 outbreak, the Indonesian government enforces the principle of social distancing at all levels of society. This researchuses a descriptive approach. Descriptive research (descriptive research) is research that is directed to provide symptoms, facts or events systematically and accurately, regarding the characteristics of a particular population or area with the type of field qualitative research (Field Research), namely research that requires Researchers go to the field to make observations about all phenomena in a state of nature. The role of PAI teachers in improving student learning achievement during the COVID-19 pandemic is very important, especially teachers are required to learn creatively and innovatively in creating learning during this COVID-19 pandemic. The conclusion of this study is that the role of teachers and the role of students is very important in seeking to improve student learning achievement during the Covid-19 pandemic. Teachers must try their best so that the learning they create makes students comfortable and understands and for students they should continue to improve their learning in order to get good learning outcomes, always motivate themselves to always enjoy learning at all times. Keyword: The Role of Teachers, Education, Covid 19 Pandemic